Bessel type Kolmogorov inequalities on weighted Lebesgue spaces. Issue 8 (11th June 2021) - Ekincioglu, Ismail; Kaya, Esra
ABSTRACT: In this paper, we obtained Bessel type Kolmogorov inequalities for Riesz–Bessel transforms related to generalized shift operator in weighted Lebesgue spaces.